Ideale vir die uitbouing van tegniese en beroepsonderwys in Suid-Afrika - Rautenbach, W. L. (Koers, 1983)
Problems emanating from the colonial structure, and which tend to reduce man to being a “human machine”, are discussed, and it is indicated that these tend to impinge on the status oj technical and professional education and lower it. From the demands the modern human-machine system makes one’s full capacity for being human, the author draws the conclusion that in technical and professional training human development has to be given primary consideration. A discussion of the problems surrounding cultural change and modernization in post-colonial set-ups indicates the fact that technical and professional education has a unique education task and opportunity in South Africa too.